National Private Banks’ Organizational Culture and Organizational Commitment Analysis - Supriyadi, Dikdik (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The acceleration of environmental change results in changes in corporate culture, the success of an organization is not only supported by the organizational culture but also how the organization fosters organizational commitment that is understood as an individual's psychological bond to the organization. The purpose of this study is to analyze the Organizational Culture and Organizational Commitment in Private Banks in Bandung. Descriptive method was used in this study for employees of some private banks. The total number of respondents were 80 employees. The result shown that Organizational Culture produces the level of effort and subordinate Organizational Commitment beyond what will happen, when viewed from the average weight of Organizational Culture. Based on the analysis of Organizational Commitment, it can be said that employees of Private Bank in Bandung as a whole have a high Organizational Commitment based on the weight generated from the questionnaires that the authors distribute.